Temporal and ontogenetic variations in feeding habits of Hollandichthys multifasciatus (Teleostei: Characidae) in coastal Atlantic rainforest streams, southern Brazil - Abilhoa,Vinícius (2009)
Feeding habits of the characin Hollandichthys multifasciatus were investigated. Samplings were made between March 2004 and February 2005 in two black water streams of the coastal Atlantic rainforest in southern Brazil. The diet, evaluated by qualitative and quantitative methods, included aquatic and terrestrial insects, decapods, oligochaetes, plants and spiders. Large individuals feed mainly on plants, terrestrial insects, and spiders, whereas small fish feed basically on plants and oligochaetes. The species showed an omnivorous feeding habit, and its diet was composed of autochthonous (mainly oligochaetes) and allochthonous (plants and terrestrial insects) material.